2016
DOI: 10.1088/1054-660x/26/2/025206
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the fidelity of molecular DNA computations: control of DNA duplex melting using Raman spectroscopy

Abstract: In this study it is demonstrated that use of laser Raman spectroscopy for monitoring biochemical reactions provides the detection and control of the processes of renaturation and denaturation of DNA strands, the determination of state of strands, and also the control of possible mutations in DNA molecules. The obtained results are very promising to improve the fidelity of DNA computations, i.e. to provide the greater convergence of the estimated and exact values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The authors of this publication have demonstrated that Raman spectroscopy allowed us to determine (in non-contact real-time mode) both the total concentration of DNA molecules in the solution and the concentration of individual nitrogenous bases in their single-component solutions, using the calibration dependencies of Raman marker bands of nitrogenous bases (figure 1) on their concentration in the range of 0 to 9 g l −1 [30,31]. Also it was shown that the use of laser Raman spectroscopy for monitoring biochemical reactions provided for the detection and control of the processes of renaturation and denaturation of DNA strands, determination of the state of the strands, and the control of possible mutations in DNA molecules [32].…”
Section: Problem Of Reliability Of Dna Computingmentioning
confidence: 99%
“…The authors of this publication have demonstrated that Raman spectroscopy allowed us to determine (in non-contact real-time mode) both the total concentration of DNA molecules in the solution and the concentration of individual nitrogenous bases in their single-component solutions, using the calibration dependencies of Raman marker bands of nitrogenous bases (figure 1) on their concentration in the range of 0 to 9 g l −1 [30,31]. Also it was shown that the use of laser Raman spectroscopy for monitoring biochemical reactions provided for the detection and control of the processes of renaturation and denaturation of DNA strands, determination of the state of the strands, and the control of possible mutations in DNA molecules [32].…”
Section: Problem Of Reliability Of Dna Computingmentioning
confidence: 99%